Formation of the Ventricles - Catherine A. Risebro; Paul R. Riley (The Scientific World Journal)
The formation of the ventricles of the heart involves numerous carefully regulated temporal events, including the initial specification and deployment of ventricular progenitors, subsequent growth and maturation of the ventricles through “ballooning” of chamber myocardium, the emergence of trabeculations, the generation of the compact myocardium, and the formation of the interventricular septum. Several genes have been identified through studies on mouse knockout and transgenic models, which have contributed to our understanding of the molecular events governing these developmental processes. Interpretation of these studies highlights the fact that even the smallest perturbation at any stage of ventricular development may lead to cardiac malformations that result in either early embryonic mortality or a manifestation of congenital heart disease.